Communicative and linguistic factors influencing language development at 30 months of age in preterm and full-term children: a longitudinal study using the CDI - Ogneva, Anastasiia; Pérez-Pereira, Miguel (Frontiers in Psychology, 2023)
Previous studies showed that very preterm children have a delay in communicative (gestures) and linguistic development as compared to full-term children. Earlier use of gestures, as well as of word comprehension and production, have been found to be predictive of subsequent word production and/or language delay in both very preterm and full-term children. Not many studies on communicative antecedents of language, however, have been carried out with low-risk preterm children in comparison to full-term children. In the present study a sample (N=142) of low-risk preterm children has been followed using the Galician version of the Communicative Development Inventories (CDI) at the ages of 10, 22 and 30 months of age and their results were compared to the results from a sample (N=49) of full-term children at the same ages. The determinants of language measures (vocabulary and grammar) at 30 months of age have been studied through linear regression analyses. ANOVA results indicate that there were no significant differences between the groups in any of the measures obtained with the CDI at any time, nor were there any differences in lexical or grammatical developmental trajectories between both groups (repeated measures ANOVA). Linear regression analyses showed that the predictors of language at 30 months of age are somewhat different for the full-term than for the preterm group. While the use of first communicative gestures at 10 months is a predictor of word production at 30 months of age for the full-term group, participation in games and routines seems to play a significant predictive role for preterm children. Word production at 22 months is the factor with a major incidence on word production at the age of 30 months for both groups. Previous specific measures of grammatical development have a clear determinant role in grammar measures at 30 months of age for the full-term children, while in the case of preterm children previous lexical development seems to be more relevant.